2001
DOI: 10.1039/b101468o
|View full text |Cite
|
Sign up to set email alerts
|

Applications of solid-phase microextraction (SPME) in the determination of residues of certain herbicides at trace levels in environmental samples

Abstract: A new analytical procedure based on solid-phase microextraction (SPME) has been developed for the determination of residues of eight selected herbicides: trifluralin, butachlor, pretilachlor, metolachlor, atrazine, acetochlor, alachlor, and fluroxypyr-meptyl, in ground water samples. Carbowax divinylbenzene was used for SPME of the herbicides. Quantification was done at equilibrium. Various parameters, such as, effect of pH, ionic strength, humic acid content and exposure time of fiber, were investigated to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…There are various methods for detection of trifluralin, including; liquid chromatography [15], gas chromatography (GC) [16], HPLC-mass spectrometry (MS) [17], UV spectrometry [18], solution-state nuclear magnetic resonance spectroscopy [19], capillary electrophoresis [20] and electrochemical methods [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…There are various methods for detection of trifluralin, including; liquid chromatography [15], gas chromatography (GC) [16], HPLC-mass spectrometry (MS) [17], UV spectrometry [18], solution-state nuclear magnetic resonance spectroscopy [19], capillary electrophoresis [20] and electrochemical methods [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The successful application of SPME to detect pollutants in trace levels in the environment like phenols in drinking water (Bartak and Cap 1997;Rodriguez et al 2000), herbicides (Ramesh and Ravi 2001), air contaminants as a result of painting and due to a jet fuel fire (Hook et al 2002), and polycyclic aromatic hydrocarbons, which are carcinogenic (King et al 2003), have been reported. From Table 6, it can be noticed that most environmental applications deal with the analysis of benzene, toleune, ethyl benzene, and xylene (BTEX) compounds.…”
Section: Spme For Similar Applications and Their Potential For Food Amentioning
confidence: 97%
“…Quantitative analysis of herbicides in soil using gas chromatography with flame ionization detection and mass spectrometry by Thijs Koelmans et al presents a study aimed at developing a sensitive and reliable method for the quantitative analysis of herbicides in soil using gas chromatography with flame ionization detection (GC-FID) and mass spectrometry (GC-MS) [61]. The authors focused on five commonly used herbicides, namely atrazine, simazine, diuron, terbuthylazine, and metolachlor, as test analytes.…”
Section: Resultsmentioning
confidence: 99%